In vivo selective expansion of a tumour-specific cytotoxic T-cell clone derived from peripheral blood of a melanoma patient after vaccination with gene-modified autologous tumour cells - Sun, Yuansheng; Schadendorf, Dirk (Immunology, 1999)
Melanoma-specific cytotoxic T lymphocytes (CTL) can be generated from peripheral blood lymphocytes (PBL) by mixed lymphocyte-tumour cell cultures. Analysis of CTL precursor frequencies in peripheral blood of melanoma patients is generally used for immunomonitoring purposes to evaluate vaccination efficacy. At present, it is unclear whether PBL-derived CTL generated in vitro are indicative of an anti-tumour immune response in vivo. Three tumour-specific human leucocyte antigen (HLA)-B/C-restricted CTL clones were derived from peripheral blood of a melanoma patient immunized with interleukin-7 (IL-7) gene-modified tumour cells. CTL clones differing in their T-cell receptor-γ (TCRγ) rearrangement produced interferon-γ, IL-4 and/or IL-10. On the basis of their unique TCRγ gene rearrangements clone-specific primers were generated for detection of clone-specific DNA by polymerase chain reaction. One CTL clone (E5) of the three was found to be selectively expanded in one of seven metastases obtained at autopsy, as determined by Southern blot hybridization. However, the presence of E5 in only one of seven metastases at death indicates that the in vivo accumulation of the specific CTL clone was not sufficient to contain tumour progression. Nevertheless, our data support the proposition that analysis of anti-tumour activity of PBL-derived CTLs may reflect an anti-tumour immune response in vivo.